2004
DOI: 10.1159/000076158
|View full text |Cite
|
Sign up to set email alerts
|

Crustacean Motor Pattern Generator Networks

Abstract: Crustacean motor pattern-generating networks have played central roles in understanding the cellular and network bases of rhythmic motor patterns for over half a century. We review here the four best investigated of these systems: the stomatogastric, ventilatory, cardiac, and swimmeret systems. Generally applicable observations arising from this work include (1) neurons with active, endogenous cell properties (endogenous bursting, postinhibitory rebound, plateau potentials), (2) nonhierarchical (distributed) n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 192 publications
(147 reference statements)
0
58
0
Order By: Relevance
“…It is clear that knowledge of synaptic connectivity of motor circuits in the absence of knowledge of the neuronal properties will be insufficient to understand motor pattern generation (Getting, 1989;Grillner, 1981;Harris-Warrick, 1993;Hooper and DiCaprio, 2004;Katz and Frost, 1996;Marder and Bucher, 2001). From studies in invertebrates, for example, it is known that the intrinsic properties of network neurones function to both generate the rhythm and to pattern the output (Getting, 1989).…”
Section: Neuronal Intrinsic Properties and Rhythm Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clear that knowledge of synaptic connectivity of motor circuits in the absence of knowledge of the neuronal properties will be insufficient to understand motor pattern generation (Getting, 1989;Grillner, 1981;Harris-Warrick, 1993;Hooper and DiCaprio, 2004;Katz and Frost, 1996;Marder and Bucher, 2001). From studies in invertebrates, for example, it is known that the intrinsic properties of network neurones function to both generate the rhythm and to pattern the output (Getting, 1989).…”
Section: Neuronal Intrinsic Properties and Rhythm Generationmentioning
confidence: 99%
“…PIR is also crucial for the timing of action potential burst onset and the pattern of firing in many rhythmic networks (Arshavsky et al, 1998;Eisen and Marder, 1984;Harris-Warrick et al, 1995b;Hartline and Gassie, 1979;Roberts et al, 1995) and may also contribute to the stability of the rhythm (Tegner et al, 1997). These data have led to the hypothesis that PIR is a desired property in rhythm-generating networks (Hooper and DiCaprio, 2004). …”
Section: Neuronal Intrinsic Properties and Rhythm Generationmentioning
confidence: 99%
“…Invertebrate nervous systems, including the crustacean stomatogastric nervous system (STNS), with its small number of large, uniquely identifiable neurons (Nusbaum et al, 2001;Skiebe, 2001;Nusbaum and Beenhakker, 2002;Fénelon et al, 2003;Fénelon et al, 2004;Hooper and DiCaprio, 2004;Marder and Bucher, 2007;Stein, 2009), have for many years provided important insights into our understanding of co-transmission (Kupfermann, 1991;Nusbaum et al, 2001;Nässel, 2009;Christie et al, 2010). In the present study, we identified the peptide co-transmitter in a pair of modulatory histaminergic projection neurons of the lobster STNS, then examined the roles played by this peptide and histamine in simultaneously modulating three different rhythmic motor patterns.…”
Section: Introductionmentioning
confidence: 99%
“…1) (Alexandrowicz, 1932;Cooke, 2002). Rhythmic behaviors, such as the neurogenic heartbeat, can be hormonally and locally modulated by neurochemicals, thus generating flexibility in the hard-wired CPG motor output (reviewed in Marder, 1991;Simmers et al, 1995;Pearson, 2000;Hooper and DiCaprio, 2004;Goulding, 2009;Guertin and Steuer, 2009;Brezina, 2010;Christie et al, 2010a;Selverston, 2010).…”
Section: Introductionmentioning
confidence: 99%